Bridging Spiritual and Social Intelligence: Integrating Spiritual and Social Intelligence in a Multicultural Society - Susanty Harahap, Fatimah Depi; M, Amril; Dewi, Eva (Al-Insyiroh: Jurnal Studi Keislaman, 2025)
This study aims to examine the integration of spiritual and social intelligence as a foundation for fostering tolerance in multicultural societies, particularly in the Indonesian context. Using a qualitative, library-based research method with a descriptive-analytical approach, the study synthesizes key theories and prior research on spirituality, social competence, and multicultural education. The findings show that spiritual intelligence—characterized by self-reflection, transcendental awareness, and universal values such as compassion and justice—provides an essential moral foundation. However, these values require the support of social intelligence—empathy, communication skills, and cultural sensitivity—to be effectively translated into inclusive social interactions. The integration of these two forms of intelligence forms a synergistic framework that strengthens tolerant character formation and supports peaceful coexistence across diverse identities. The study concludes that fostering tolerance requires not only legal and structural measures but also cultural and educational strategies that integrate spiritual reflection with social skills training. Practically, the findings suggest that character education, interfaith learning spaces, and multicultural training programs can serve as effective platforms to nurture inclusive citizenship in plural societies.